Pag gene based phylogenic characterization of Bacillus anthracis from sheep - CHANDRANAIK, B M; D’SOUZA, CHARRISE R; RAJASHEKAR, BIRADAR; SREEVATSAVA, V; SHIVASHANKAR, B P; NANDINI, POOJAPPA; GOMES, AMITHA REENA; GIRIDHAR, P; BYREGOWDA, S M (The Indian Journal of Animal Sciences, 2017)
We report the protective antigen gene based molecular epidemiology of a massive anthrax outbreak in sheep that killed over 100 sheep. The outbreak was unique since the use of higher antibiotics immediately after the live anthrax vaccine had facilitated wide spread of the disease and unscientific disposal of carcasses had precipitated the disease magnitude. B. anthracis was isolated from ear blood samples collected from dead sheep. The isolates were non-motile, non-hemolytic and were pathogenic to mice. Gene coding for the toxic factor 'protective antigen' was targeted for PCR amplification as per WHO and OIE protocols. Sequencing of nucleotides on the conserved pag gene showed that the B. anthracis isolated during this study shared a sequence identity of more than 99.9% with B. anthracis isolates from different species, including human beings. The phylogeny demonstrated the genetic stability of the immunologically protective pag gene across species.